Aborted microspores acts as a master regulator of pollen wall formation in Arabidopsis - Xu, Jie; Ding, Zhiwen; Vizcay-Barrena, Gema; Shi, Jianxin; Liang, Wanqi; Yuan, Zheng; Werck-Reichhart, Danielle; Schreiber, Lucas; Wilson, Zoe A.; Zhang, Dabing (American Society of Plant Biologists, 2014)
Mature pollen is covered by durable cell walls, principally composed of sporopollenin, an evolutionary conserved, highly resilient, but not fully characterized, biopolymer of aliphatic and aromatic components. Here, we report that ABORTED MICROSPORES (AMS) acts as a master regulator coordinating pollen wall development and sporopollenin biosynthesis in Arabidopsis thaliana. Genome-wide coexpression analysis revealed 98 candidate genes with specific expression in the anther and 70 that showed reduced expression in ams. Among these 70 members, we showed that AMS can directly regulate 23 genes implicated in callose dissociation, fatty acids elongation, formation of phenolic compounds, and lipidic transport putatively involved in sporopollenin precursor synthesis. Consistently, ams mutants showed defective microspore release, a lack of sporopollenin deposition, and a dramatic reduction in total phenolic compounds and cutin monomers. The functional importance of the AMS pathway was further demonstrated by the observation of impaired pollen wall architecture in plant lines with reduced expression of several AMS targets: the abundant pollen coat protein extracellular lipases (EXL5 and EXL6), and CYP98A8 and CYP98A9, which are enzymes required for the production of phenolic precursors. These findings demonstrate the central role of AMS in coordinating sporopollenin biosynthesis and the secretion of materials for pollen wall patterning.